Screen Printing Conductive Inks on Textiles: Impact of Plasma Treatment - Julia Guérineau; Jollan Ton; Mariia Zhuldybina (Sensors)
Textile-based wearable devices are rapidly gaining traction in the Internet of Things paradigm and offer distinct advantages for data collection and analysis across a wide variety of applications. Seamlessly integrating electronics in textiles remains a technical challenge, especially when the textiles’ essential properties, such as comfort, breathability, and flexibility, are meant to be preserved. This article investigates screen printing as a textile post-processing technique for electronic integration, and highlights its versatility, cost-effectiveness, and adaptability in terms of design and customization. The study examines two silver-based inks screen-printed on an Oxford polyester textile substrate with a focus on substrate preparation and treatment. Before printing, the textile samples were cleaned with nitrogen gas and then subjected to low-pressure oxygen plasma treatment. For comparative analysis, two samples printed on polyethylene terephthalate (PET) serve as a reference. The findings highlight the importance of plasma treatment in optimizing the printability of textiles and demonstrate that it notably improves the electrical properties of conductive inks. Despite some remaining challenges, the study indicates that screen-printed electronics show promising potential for advancing the development of e-textiles and sensor-integrated wearables.